simulation and virtual reality in teaching-learning processes in health care training. - Roa Cartagena, Marly
The clinical simulation uses several modalities that allow some clinical environments to be recreated in an academic context to educate, train or evaluate people or teams before interacting with the real patient. These modalities include task trainers, standardized virtual patients, high-fidelity, and reality simulators. The contribution of virtual reality environments to the transfer between theory and practice is emphasized, and at the same time, they increase the motivation of the students. Objective: This review aims to identify the contribution of simulation with virtual reality in teaching-learning processes, in the training of health care professionals. Methodology: A documentary review of electronic national and international indexed journals was carried out. First, the keywords were established for the search in databases, then the information of the selected articles was collected in a systematic review matrix for their respective analysis. Results: The use of virtual reality in health education, allows students to have experiences that bring them closer to reality, it is an interactive technique that is presented in a creative and motivating way, allowing the development of different learning styles, awakening the interest of those who use it and at the same time raising the knowledge levels. Conclusions: The use of simulation with Virtual Reality in the teaching-learning processes of health training is a valuable tool that develops student leadership, creativity, safety, teamwork, innovation, and collaborative work, allowing to strengthen skills and abilities towards patient’s care.